The Role of Vitamin D and Its Receptor Signaling in Diabetic Nephropathy and the Current Status of Research: A Literature Review - Qiaoya He; Jiaqi An; Xinze Liu; Li Zhuo (Acta Medica Indonesiana, 2025)
Diabetic kidney disease (DKD) is one of the common and serious complications of diabetes mellitus, with a complex pathogenesis and a lack of ideal treatment options in clinical practice. In recent years, the protective role of vitamin D and its receptor signaling pathway in DKD has garnered widespread attention. Vitamin D plays an important role in the onset and progression of DKD by participating in the regulation of insulin secretion, inhibiting inflammatory responses, attenuating podocyte injury, modulating the renin-angiotensin system (RAS), and inhibiting renal interstitial fibrosis through its receptor (VDR). Studies on the use of vitamin D and its receptors in DKD have increased gradually in recent years, with a focus on the development of vitamin D analogs and the clinical application of VDR activators. This study reviewed the mechanisms of vitamin D and its receptor in diabetic nephropathy, as well as the potential for therapeutic applications and associated adverse effects. It also analyzed current research hotspots and development trends based on bibliometrics. Future research should focus on further optimizing vitamin D-based therapeutic strategies to achieve better clinical efficacy and safety.